The role of collegial alliance in family‐based treatment of adolescent anorexia nervosa: A pilot study. Issue 4 (26th November 2013) - Murray, Stuart B.; Griffiths, Scott; Le, Daniel
ABSTRACT Objective In keeping with broader efforts to identify mediators and moderators of treatment outcome in anorexia nervosa, this pilot study investigated the association between collegial alliance, which refers to the perceived alliance between case‐involved professionals, and treatment outcomes in adolescent patients undergoing family‐based treatment (FBT) for anorexia nervosa. Method The self‐reported collegial alliance scores of five FBT practitioners were collected, alongside weight‐ and cognitive‐related outcomes for 29 consecutive cases of adolescent anorexia nervosa under their care. Results Collegial alliance discriminated between patients who dropped out of treatment and patients who completed treatment, t(27) = 3.68, p = .001, η2 = .33. Furthermore, there was a strong negative correlation between collegial alliance scores early on in treatment and disordered eating symptoms later in treatment, r(23) = −.67, p < .001. Moderate but non‐significant associations were observed between early collegial alliance and patient's percentage of expected body weight later in treatment, r(23) = .32, p = .13. Discussion These findings have important implications for the augmentation of FBT, suggesting that unity amongst clinicians promotes positive treatment outcomes, particularly with regard to disordered eating symptomatology. © 2013 Wiley Periodicals, Inc. (Int J Eat Disord 2014; 47:418–421)